Design of multistage fixed bed reactors for SMR hydrogen production based on the intrinsic kinetics of Ru-based catalysts. (15th September 2022) - Lee, Jaewon; Joo, Chonghyo; Cho, Hyungtae; Kim, Youngjin; Ga, Seongbin; Kim, Junghwan
Graphical abstract: Highlights: On-site hydrogen refueling stations require efficient catalysts/reactors. Intrinsic kinetics of Ru catalysts were estimated using a parametric estimation. New multistage (two- and three-stage) reactor designs were proposed. Multistage reactors showed less temperature drop (better reactor stability). Three-stage reactor can improve hydrogen production and conversion. Abstract: In recent years, interest in the development of a hydrogen economy has increased, and the steam methane reforming (SMR) reaction, which yields so-called "gray" hydrogen, is expected to play a key role in hydrogen refueling stations (HRSs) in the interim before "green" hydrogen process is developed. For this purpose, compact and economical designs for small- to medium-scale SMR processes for HRSs are required. Herein, we investigated the intrinsic kinetics of a Ru-based catalyst using catalyst experiments and parametric estimation. In addition, reactor modelling was performed using a kinetic model with a special focus on multistage reactor configurations. The proposed reactor design showed an increase in the reactor energy supplied rate from 6.98 to 7.55 kW compared to the base case (single-stage reactor), and the conversion increased from 86.2% to 91.2%. Further, the drastic temperature drop owing to the strongly endothermic nature of the SMR reaction was reduced, and, thus, reactor stability was improved. The proposed novel design of a multistage reactor using a Ru-based catalyst will advance the development of the hydrogen economy.